Epigenetic Regulation of Enteric Neurotransmission by Gut Bacteria - Savidge, Tor C. (Frontiers in Cellular Neuroscience, 2016)
The Human Microbiome Project defined microbial community interactions with the human host, and provided important molecular insight into how epigenetic factors can influence intestinal ecosystems. Given physiological context, changes in gut microbial community structure are increasingly found to associate with alterations in enteric neurotransmission and disease. At present, it is not known whether shifts in microbial community dynamics represent cause or consequence of disease pathogenesis. The discovery of bacterial-derived neurotransmitters suggests further studies are needed to establish their role in enteric neuropathy. This mini-review highlights recent advances in bacterial communications to the autonomic nervous system and discusses emerging epigenetic data showing that diet, probiotic and antibiotic use may regulate enteric neurotransmission through modulation of microbial communities. A particular emphasis is placed on bacterial metabolite regulation of enteric nervous system function in the intestine.